Tеоретические аспекты формирования пассивов коммерческих банков - Кантур, С.Ф.; Кашкина, О.П. (Культура народов Причерноморья, 2013)
В статье приведены разные трактовки понятия «пассивы банка», определены источники
формирования пассивов банка, дана краткая характеристика построения собственных, привлеченных и
заемных средств и функциональной направленности пассивов банка. Определена роль и значение
пассивов для банковской деятельности и для обеспечения его финансовой устойчивости.
Ключевые слова: коммерческий банк, пассивы, ресурсы банка, привлеченные средства, заемные
средства, банковская деятельность, финансовая устойчивость, ликвидность банка,
платежеспособность банка. У статті приведені різні трактування поняття «пасиви банку», визначені джерела
формування пасивів банку, дано коротку характеристику побудови власних, залучених та позичених
коштів та функціональної спрямованості пасивів банку. Визначено роль та значення пасивів для
банківської діяльності та для забезпечення його фінансової стійкості.
Ключові слова: комерційний банк, пасиви, ресурси банку, залучені кошти, позичені кошти, банківська
діяльність, фінансова стійкість, ліквідність банку, платоспроможність банку. The article presents the different interpretations of the notion «liabilities of the Bank», identified
sources of the Bank's liabilities, given a short characteristics of construction of own and attracted and borrowed
funds and functional orientation of the Bank's liabilities. Determined the role and the value of the liabilities of
the Bank for banking activity and for ensuring financial stability of the Bank. In modern conditions of economic
development, the problem of formation of resources has a paramount importance. Banks are playing a major
role in the formation of optimal environment for the mobilization and free float of capital, accumulation of funds
for the structural adjustment of the economy, and business development. Commercial banks carry out active and
passive operations. Passive operations it is attracting Bank funds at the expense of own and borrowed sources
with the purpose of creation of credit resources. Research of activity of commercial banks should start with a
debit balance, which characterizes the sources of funds and the nature of the financial relations of the Bank,
because it is passive operations to a large extent determine the conditions, forms and directions of the use of
Bank resources, that is, the composition and structure of assets. But all, without exception, conducted by the
Bank's operations have a single goal - increase of income and reduction of expenses of the Bank. Thus, the
problem of formation of Bank liabilities is very important for the success of a commercial Bank.
Key words: commercial bank, liabilities, bank resources, attracted resources, borrowed assets, banking activity,
financial stability, banks liquidity, the solvency of the Bank.